Various doses of statins and coronary angiogenesis in patients with coronary heart disease - I. V. Sergienko; A. E. Semenova; V. V. Masenko; S. A. Gabrusenko; V. V. Kukharchuk; Yu. N. Belenkov (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To investigate the effects of different doses of statins on the levels of factors stimulating and inhibiting coronary angiogenesis.Material and methods. The study included 90 patients with coronary heart disease (CHD), Functional Class I-III stable angina, and 30 healthy volunteers. All patients underwent clinical examination, electrocardiography, veloergometry, and echocardiography. At baseline, blood lipid levels were measured. Serum levels of vascular endothelial growth factor (VEGF), transforming growth factor (TGF-pi), and endostatin were measured twice — before statin therapy and 3 months after it started. Daily rosuvastatin dose was 5, 10, or 40 mg.Results. Statin therapy resulted in reduced levels of angiogenesis-stimulating factors, such as VEGF and TGF. The level of endostatin, which inhibits angiogenesis, did not change substantially. Similar effects were observed for doses of 5, 10, and 40 mg/d.Conclusion. The results obtained disagree with the hypothesis of dose-dependent effects of statins on angiogenesis. Both low doses of statins and aggressive statin therapy affect angiogenesis factors similarly.